2017
DOI: 10.1038/ncb3451
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Corrigendum: Translocon component Sec62 acts in endoplasmic reticulum turnover during stress recovery

Abstract: In this Article, we reported that G9a promotes colorectal-cancer-initiating cell self-renewal and function by repressing Let-7b expression in a manner independent of its enzymatic activity, thereby activating K-RAS and β-catenin signalling. However, it has come to our attention that during figure assembly certain images were inappropriately processed and duplicated in several figures of the article, including Figs 1d, 2d, 3b, 5a, 5f, 6h and 8f. In light of these errors and image reuse in multiple figures we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Autophagy receptors are characterized by an LC3-interacting region (LIR). Binding of the ubiquitin-like protein LC3-II to LIR triggers selective autophagy [ 62 ]. The conserved LIR motif was found in the C-terminus of human Sec62 (NDFEMIT, residues 461–367) and is important for Sec62-mediated selective autophagy of the ER components after an unfolded protein response.…”
Section: Additional Functions Of Sec62 and Sec63 In Mammalsmentioning
confidence: 99%
“…Autophagy receptors are characterized by an LC3-interacting region (LIR). Binding of the ubiquitin-like protein LC3-II to LIR triggers selective autophagy [ 62 ]. The conserved LIR motif was found in the C-terminus of human Sec62 (NDFEMIT, residues 461–367) and is important for Sec62-mediated selective autophagy of the ER components after an unfolded protein response.…”
Section: Additional Functions Of Sec62 and Sec63 In Mammalsmentioning
confidence: 99%
“…Another molecular chaperone, Sec62, is an essential component of the posttranslational translocation machinery in the ER. A study identified Sec62 as a critical molecular component in the maintenance and recovery of ER homeostasis (42). DNAJA1 is an essential cochaperone of mammalian heat shock cognate 70 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, large bulk proteins and aggregates can be targeted for lysosomal degradation via ER-phagy, which is a selective form of autophagy that protects the cells from excessive ER stress (Mochida et al, 2015;Chino and Mizushima, 2020). ER-phagy receptors, such as FAM134B and SEC62, reside in specific structures of the ER; FAM134B is found in curved portions of the ER membrane while SEC62 is found in flat portions of the ER sheets (Khaminets et al, 2015;Fumagalli et al, 2016). These receptors respond to cell stress resulting from misfolded protein accumulation, starvation, and calcium imbalance within the ER lumen and link their respective ER domains to autophagy machinery (Grumati et al, 2018).…”
Section: Clearance Of Unfolded Proteins Is An Indispensable Component...mentioning
confidence: 99%